Evaluation of the CPR video decision aid with patients with end stage renal disease - Kapell Brown, Cherie (BMC Nephrol, 2018)
BACKGROUND: People with end stage renal disease (ESRD) face important health-related decisions concerning end-of-life care and the use of life-support technologies. While people often want to be involved in making decisions about their health, there are many challenges. People with advanced illness may have limited or wavering ability to participate fully in decision-making conversations – or lack decisional capacity for making decisions. Additionally, they may have a limited understanding of CPR and tend to receive inconsistent information on the process and outcome of CPR. Unfortunately, these discussions are often avoided. Shared decision-making approaches are an approach to overcoming these challenges. The objectives of this research was to design, test, and analyze a novel CPR video decision aid (VDA) with nephrology patients and their families in a clinical setting. METHODS: The Interprofessional Shared Decision-making Model was used as a framework to guide the research. A prospective quasi-experimental design included pre/posttest measures of knowledge and confidence in decision-making, and posttest only measure of uncertainty about the decision. RESULTS: Participant knowledge about CPR increased from a mean score of 4.8/9 (standard deviation [SD] = 1.65) before viewing the video to 7.5/9 (SD = 1.40) (p = 0.000) after viewing the video. Decisional self-efficacy improved slightly from 84% pre intervention (SD 17.04, range 20–100) to 86% after the intervention (SD 14.13, range 39–100) (p = 0.005) for patient participants. Before the intervention, most patients (43/49; 86%) had an order to have CPR in the physician orders and very few (7/49; 14%) had an order not to have CPR. Immediately after viewing the CPR-VDA and completing the values clarification worksheet, fewer 28/49 (57%) chose to have CPR, 13 (27%) chose not to have CPR and 8 (16%) were unsure. CONCLUSIONS: The CPR-VDA was feasible and acceptable to patients with ESRD, their families and the healthcare team. The CPR-VDA positively affected decision-making: improving patient and family knowledge about CPR, clarity of values, patients’ decisional self-efficacy, the congruence between documented physician’s orders and patient choice, quality of communication about CPR, while reducing decisional conflict (uncertainty) amongst patients, families, and physicians.